Escassez de crédito bancário no Brasil: comparação internacional e evidência recente - Gomes, Dioscoro Mesquita (2009)
The objective of this work is to examine the level of bank credit in Brazil in the period after the Real Plan. To this, the work uses the Barajas and Steiner (2002) methodology but with a larger country sample (Brazil among nine Latin American countries and other forty outside Latin America). The results suggest that bank credit has not grown as expected and is still as volatile as the Latin America average. The size of the Brazilian banking system is not small as expected, but is less prone to lending to the private sector. Credit to the public sector still occupies a very important share of the Brazilian banking system balance sheet. About this matter the work shows that an increase in securitization could increase significantly the credit to the private sector.